A&T Bangladesh Urban Maternal Nutrition Baseline Survey 2020: Health Facility Assessment - International Food Policy Research Institute (International Food Policy Research Institute, 2021)
This dataset is the result of the health facility assessment survey that was conducted to gather data for the baseline part of the impact evaluation study of the Alive & Thrive (A&T) interventions delivered through the Urban Maternal, Neonatal and Child Health (MNCH) Services in Bangladesh. These include building capacity for health providers and nutritional counselors in urban health clinics, creating a friendly environment for maternal infant, and young child nutrition (MIYCN) counseling in clinic settings, community mobilization for demand creation of MIYCN services, interpersonal counseling on diet during pregnancy and consumption of iron folic acid (IFA) and calcium, promotion of adequate weight-gain monitoring during pregnancy, and counseling on breastfeeding and complementary feeding practices. A&T is a global initiative that supports the scaling up of nutrition interventions to save lives, prevent illnesses, and contribute to healthy growth and development through improved maternal nutrition, breastfeeding, and complementary feeding practices. Using a quasi-experimental design, the primary objectives of the A&T evaluation study in Bangladesh are to answer the following questions: 1) Is it feasible to standardize the delivery of MIYCN counseling services in existing urban health facilities? 2) Can the quality of MIYCN counseling services be improved by upgrading and standardizing existing MIYCN counseling services in urban health facilities? 3) What are the impacts of standardized and upgraded MIYCN counseling services on the utilization of MIYCN services? 4) What are the impacts of standardized and upgraded MIYCN counseling service on the knowledge and behaviors of clients including: 4.1) Pregnant women: 1) consumption of diversified foods; 2) intake of IFA and calcium supplements during pregnancy 4.2) Mothers of children <1 y: age-appropriate infant feeding The baseline survey used 24 facilities in Dhaka, Bangladesh, with a non-random assignment of facilities to the intervention and control groups. Eight facilities from two NGOs of Radda and Marie Stopes received the intervention, while sixteen facilities operated by Nari Maitree and Shimantik served as the comparison group. The survey took place in October 2019 and February-March 2020 by the team from International Food Policy Research Institute (IFPRI), in collaboration with the survey firm, DATA (Data Management and Technical Assistance). The baseline survey comprised four questionnaires: 1) health facility assessment; 2) provider survey; 3) case observations and 4) client interviews. The health facility assessment contained modules related to facility infrastructure, services provided to women and children, service readiness, caseload, and availability of trained providers.